Influencers in Luxury Brand Communication: An Evaluation of the Relationship Between Source Credibility, Persuasive Message, and Parasocial Engagement - Alkan, Zeynep; Dolunay, Ayhan; Ulas, Sevilay (Sage Publications Inc, 2025)
This study examines persuasive messages and source credibility in luxury brand influencers' content within their brand collaborations. It also explores how influencers establish parasocial engagement with followers through their posts. Conducted as an online survey between February and July 2023, the study targeted 400 individuals in Northern Cyprus who follow influencers. Findings indicate that increased parasocial engagement enhances the perceived persuasiveness of messages. A positive relationship between parasocial engagement and source credibility was observed, demonstrating that as influencers' credibility rises, so does the persuasiveness of their messages. Additionally, the study analyzed relationships between parasocial engagement, persuasive messages, source credibility and demographic factors. While no significant differences were found between parasocial engagement and most demographic characteristics, education level stood out. Individuals with a primary education level showed a greater tendency toward parasocial engagement. A significant difference was noted between source credibility and monthly income, with the highest perceived credibility reported in the 7,000 to 8,999 TL income group. Similarly, persuasive messages were most effective among individuals in this income range. In conclusion, this study highlights the importance of considering demographic differences and parasocial engagement in influencer brand collaborations. It underscores that source credibility and persuasive messages play a crucial role in influencer communication, influencing how audiences perceive and engage with branded content. It has been concluded that strong parasocial bonds in influencer and brand collaborations play a strategic role in establishing effective interaction with the target audience.
Keywords: Influencer; Influencer Communication; Parasocial Engagement; Source Credibility; Persuasive Message